The extent, determinants and uses of corporate internet reporting in Malaysia - Siti Zaidah Binti Turmin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
The widespread and increasing use of Internet technology in human life is undeniable. The Internet is accepted as an extremely important new technology in the business world and the use of Internet technology that is aligned with the organisational goals are considered a precondition for a company's success (Porter, 2001). The Internet facilitates communication in the business world. The communication process between the corporate sector and stakeholders via the medium of the Internet is specifically called Corporate Internet Reporting (CIR). CIR consists of the financial and non-financial information provided by companies through the medium of corporate websites (Kerckhoven, 2002). This study is conducted with the objective of examining the extent and determinants of CIR practised by public listed companies in Malaysia, the reasons for companies to practise or not to practise CIR, and the usage of CIR among stakeholders in Malaysia. The study uses a sample of 380 companies from the Main and ACE markets and 351 corporate information users consisting of institutional investors, fund managers, investment analysts, auditors and loan managers. Instruments of measurement used are unweighted index of 41 CIR attributes and two sets of questionnaires. Data is analysed by using various statistical tests –descriptive, correlation, regression, Mann-Whitney U Test, ANOVA, Independent Sample T-Test and Chi-square Test. Although the study found that 82 per cent of companies have websites and are practicing CIR, on average, companies only exhibited 28.9 percent of CIR attributes. Size, profitability and the activity sector are found to be a significant influence on the extent of CIR practice, while liquidity, auditor type, leverage, independent directors and ownership structure are not significant. The study reveals that the most important reasons for companies to practice CIR are companies' acceptance of CIR as a norm in today's business world, ability of CIR in providing very timely and more information to stakeholders, aspiration of companies to be in line with technological development and availability of data downloading and processing by stakeholders. On the contrary, users' request and preference over the traditional paper-based corporate reporting, companies' concern on the security of information being presented as well as consideration of cost and time are found to be the important reasons for companies not to practice CIR. Furthermore, the study found that downloads of financial statements, annual reports and other financial documents are the most used CIR items while sitemap and internal search engines are the commonly used website functionalities. This study has implications on companies, users and accounting regulatory bodies in Malaysia as well as on Internet reporting knowledge and literature. The findings, motivation, implications and limitations of the study as well as the suggestions for future research are discussed extensively in the study.